Subcritical Water Extraction of Phenolic Compounds from Moringa Oleifera Leaf - Siti Zullaikah; Irfan Saputra; Ghuzrina Prihandini; M. Rachimoellah (Institut Teknologi Sepuluh Nopember, 2014)
Moringa oleifera leaf is a good source of phenolic compounds that are reported to exhibit antioxidant activity both in vitro and in vivo. This study investigated the extraction of phenolic compounds from Moringa oleifera leaf using subcritical water. Experiments were performed in a batch stainless steel reactor at temperature ranging from 100 to 300oC at residence time of 5 to 20 min. Subcritical water extraction resulted the highest yield of product, total phenolic compounds and antioxidant activity at temperature of 200oC at residence time of 15 minutes. The yield of product, total phenolic compounds and antioxidant activity obtained were 30.661%, 48.733 mg tannat acids/ g dry powder of extract and 45.863 mg ascorbic acid/L, respectively. Subcritical water at 200°C and 15 min might be a good substitute to organic solvents such as ethanol to obtain phenolic compounds from Moringa oleifera leaf.